Competencia digital docente para la inclusión y la cohesión social en los procesos de enseñanza: experiencia chilena durante el COVID-19 / Digital teaching competence for inclusion and social cohesion in teaching processes: Chilean experience during COVID-19 - Leonardo Alberto Velásquez-Castro; Jorge Martín-Domínguez; Elena Ramírez-Orellana (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2023)
This study examined teacher digital competence training for inclusion and social cohesion in Chile during the Covid-19 confinement. The objective was to analyze how teachers are trained in ICT and how they use these tools to develop distance education processes. The methodology used was a quantitative approach through a descriptive design of a multiple-choice questionnaire. The findings indicate that ICT training occurs mainly as a spontaneous process of self-learning by the teacher and that their motivations for training in ICT respond mainly to the desire to improve their professional skills. Teachers highly value training processes to develop distance education processes around the use of technologies. The teachers who adapted their planning for the new distance education are those who carried out self-learning processes and have training in technological tools. Most teachers opted for a mixed approach in content delivery and complemented classes through video calling platforms with tools for asynchronous work. Regarding evaluation processes, teachers certainly know that clear and precise instructions are relevant in distance education.